The Bradykinin B2 Receptor Agonist (NG291) Causes Rapid Onset of Transient Blood–Brain Barrier Disruption Without Evidence of Early Brain Injury - Rodríguez-Massó, Sergio R.; Erickson, Michelle A.; Banks, William A.; Ulrich, Henning; Martins, Antonio Henrique (Frontiers in Neuroscience, 2021)
Background: The blood-brain barrier (BBB) describes the brain’s highly specialized capillaries, which form a dynamic interface that maintains central nervous system (CNS) homeostasis. The BBB supports the CNS, in part, by preventing the entry of potentially harmful circulating molecules into the brain. However, this specialized function is challenging for the development of CNS therapeutics. Several strategies to facilitate drug delivery into the brain parenchyma via disruption of the BBB have been proposed. Bradykinin has proven effective in disrupting mechanisms across the blood-tumor barrier. Unfortunately, bradykinin has limited therapeutic value because of its short half-life and the undesirable biological activity elicited by its active metabolites. Objective: To evaluate NG291, a stable bradykinin analogue, with selective agonist activity on the bradykinin-B2 receptor and its ability to disrupt the BBB transiently. Methods: Sprague Dawley rats and CD-1 mice were subjected to NG291 treatment (either 50µg/kg or 100µg/kg, intravenously). Time and dose-dependent BBB disruption were evaluated by histological analysis of Evans blue extravasation. Transcellular and paracellular BBB leakage were assessed by infiltration of 99mTc-Albumin (66.5KDa) and 14C-Sucrose (340Da) radiolabeled probes into the brains of CD-1 mice treated with NG291. NG291 influence on P-gp efflux pump activity was evaluated by quantifying the brain accumulation of 3H-verapamil, a known P-gp substrate, in CD-1 mice. Results: NG291-mediated BBB disruption was localized, dose-dependent, and reversible as measured by Evans blue extravasation. 99mTc-Albumin leakage was significantly increased by 50µg/kg of NG291, whereas 100µg/kg of NG291 significantly augmented both 14C-Sucrose and 99mTc-Albumin leakage. NG291 enhanced P-gp efflux transporter activity and was unable to increase brain uptake of the P-gp substrate pralidoxime. NG291 did not evoke significant short-term neurotoxicity, as it did not increase brain water content, the number of Fluoro-Jade C positive cells, or astrocyte activation. Conclusion: Our findings strongly suggest that NG291 increases BBB permeability by two different mechanisms in a dose-dependent manner and increases P-gp efflux transport. This increased permeability may facilitate the penetration into the brain of therapeutic candidates that are not P-gp substrates.